CLARIFYING THE LAW OF COMPLICITY S v Mbuyisa [2023] ZAKZPHC 132; 2023 JDR 4950 (KZP) - Shannon Hoctor (Obiter, 2024)
The single perpetrator is the paradigmatic offender. Apart from very limited exceptions, all the elements of criminal liability, including both actus reus and mens rea, apply to the perpetrator, and a conviction cannot ensue unless the presence of each element is established, and the blameworthiness of the accused is duly considered to be proved beyond reasonable doubt. The problems posed by complicity (more commonly described as participation in South African law) emerge where more than one person is involved in criminal conduct, and yet, the rules governing criminal liability in respect of groups of two or more offenders do not admit of collective responsibility, but depend on the individual contribution of the participant to the criminal enterprise, and the application of the elements of liability to such contribution. The question of the operation of the rules governing co-perpetrator liability and common purpose has frequently arisen in the courts and in academic writing on criminal law. These issues once again arose for consideration in the recent case of S v Mbuyisa ([2023] ZAKZPHC 132; 2023 JDR 4950 (KZP)), which is discussed below.